2006
DOI: 10.1002/jnr.20830
|View full text |Cite
|
Sign up to set email alerts
|

Fos‐enkephalin signaling in the rat medial vestibular nucleus facilitates vestibular compensation

Abstract: In the present study, we first observed up-regulation in preproenkephalin (PPE)-like immunoreactivity (-LIR), a precursor of Met- and Leu-enkephalin, in the rat ipsilateral medial vestibular nucleus (ipsi-MVN) after unilateral labyrinthectomy (UL). By means of double-staining immunohistochemistry with PPE and Fos, a putative regulator of PPE gene expression, we revealed that some of these PPE-LIR neurons were also Fos immunopositive. The time course of decay of these double-stained neurons was quite parallel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition, in the vestibular compensation produced after an unilateral labyrentectomy, the inhibition of the I Ca may contribute to vestibular plasticity through the modulation of gene expression (Kitahara et al, 2006; Catterall, 2011; Beraneck and Idoux, 2012). The accuracy of the vestibular system critically depends on the balance between the gains of both vestibules (Sadeghi et al, 2009; Cullen, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the vestibular compensation produced after an unilateral labyrentectomy, the inhibition of the I Ca may contribute to vestibular plasticity through the modulation of gene expression (Kitahara et al, 2006; Catterall, 2011; Beraneck and Idoux, 2012). The accuracy of the vestibular system critically depends on the balance between the gains of both vestibules (Sadeghi et al, 2009; Cullen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recordings in slices obtained from the medial vestibular nucleus (MVN) of the rat have shown that delta-opioid receptor agonists decreased the neuronal tonic discharge (Sulaiman and Dutia, 1998). Further, the use of preproenkephalin antisense and naloxone significantly delayed vestibular compensation (Kitahara et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Unilateral labyrinthectomy causing vestibular behavioral deficits was accompanied by pre-pro-Enk up regulation and increased Fos activity in the medial vestibular nucleus. Blockade of this up regulation with naloxone or antisense probes increased the behavioral deficits (590). DYN anti-sera applied soon after spinal cord ischemia attenuated NOS up-regulation, and reduced both spinal edema and cell injury (1022).…”
Section: B Neurological Disordersmentioning
confidence: 99%
“…On the other hand, as fos can form heterodimeric AP-1 complexes binding to AP-1 sites on different gene promoters, it can upregulate preproenkephalin mRNA, a precursor of Met- and Leu-enkephalin in ipsilateral MVNs after UL, for the preproenkephalin gene has a DNA binding site (AP-1) in its promoter region [21, 22]. It was said that this Fos-preproenkephalin signaling in the ipsilateral MVNs could be effective mainly at the chronic stage rather than at the very early stage.…”
Section: Discussionmentioning
confidence: 99%